Challenges for assisted reproduction and secondary infertility in Latin America - Luna, Florencia (2013)
This essay explores a new way to think about Assisted Reproductive Technologies (ARTs) in the Latin American context. The infertility caused by inadequately treated sexually transmitted diseases and by unsafe or illegal abortions is preventable, neglects women´s sexual health, and disproportionally affects the region’s poorest women. I suggest a new logic that revisits ARTs to do justice to the relevance of this type of infertility. I propose to utilize these technologies so as to transform the care of women and open a new discourse. I also suggest we should be more strategic and seek new alliances.